PROFESSIONAL COMPETENCY OF BIOLOGICAL EDUCATION STUDENTS IN THE IMPLEMENTATION OF GUIDED TEACHING - Desi Sakinah Tinendung; Cicik Suriani; A Aryeni (Universitas Negeri Medan, 2021)
This study aims to determine the perception of biology tutors on the professional competence of biology students in the implementation of guided teaching at SMA Negeri Medan T.A 2019/2020. This type of research is descriptive research. The population in this study was 14 people (3 men, 11 women) biology tutors at SMA Negeri in Medan City. The sample used in this study was 14 biology tutors, who were taken by total sampling. The instrument used in this research is a questionnaire. Questionnaires were used to collect data on the perception of biology tutors on the professional competence of biology students in the implementation of guided teaching. The results of this study indicate that the perception of biology tutors on the ability to master the material is 79%, open lessons 81%, ask 78%, carry out variations in learning 80%, ability in clarity and presentation of material 85%, managing class 84%, closing lessons 81% and adjust between time and subject matter 85%. Overall, the perception of civil servant teachers on the professional competence of biology students is very good (81.62%).